Detecting a Novel Walking-Based Performance Fatigability Marker With Accelerometry in Older Adults. (17th December 2021) - Harezlak, Jaroslaw; Boudreau, Robert; Urbanek, Jacek; Moored, Kyle; Schrack, Jennifer; Simonsick, Eleanor; Glynn, Nancy W; Qiao, Yujia (Susanna)
Abstract: Walking-based performance fatigability measures (e.g., lap-time difference) may not adequately capture performance deterioration as self-pacing is a common compensatory strategy in those with low activity tolerance. To overcome this limitation, we developed a new approach with accelerometry (ActiGraph GT3X+, sampling=80 Hz, non-dominant wrist) during fast-paced 400m-walk (N=57, age=78.7±5.7 years, women=53%). Cadence (steps/second) was estimated using raw accelerometer data (R "ADEPT"). Penalized regression splines (R "mgcv") were used to estimate the individual-level smoothed cadence trajectories. "Time-to-slow-down" was defined as first time-point where the full confidence interval of change in cadence<0. Five participants were censored at stopping time (not slowdown or complete walk). Median "time-to-slow-down" was 1.86 minutes (IQR=0.98-2.73, range=0.57-6.25). Participants with longer "time-to-slow-down" had slower starting cadence, longer 400m-walk time, and greater perceived fatigability (Pittsburgh Fatigability Scale), p's<0.05 (linear regression). Our preliminary findings revealed that detecting accelerometry-based performance fatigability/deterioration in older adults is feasible and needs to account for initial pace.